PENGARUH PENDAPATAN DAN PAJAK TERHADAP LABA BERSIH PADA PT. BHARTI NOORGRAHA SEJATI - HERMANTO HERMANTO; YUDA REMOFA; FATTI CORRINA (Fakultas Ekonomi Universitas Islam Indragiri, 2023)
This research was conducted to examine the effect of income and taxes on net income at PT. The True Bharti Noorgraha. The research method uses quantitative with secondary data sources, the data is processed using the help of the IBM SPSS version 21 program. The results of the study show that income and taxes simultaneously affect net profit at PT. Bharti Noorgraha Sejati, partially income and taxes have an effect on net profit at PT. Bharti Noorgraha Sejati